2019
DOI: 10.35940/ijitee.i8197.0881019
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Conventional Pcc Strength And Durability with Partial Replacement of Cement using Aluminium Powder and Rice Husk Ash

Abstract: Bond is generally noted to be most costly constituents of cement. The whole development industry is looking for an appropriate and viable the waste item that would extensively limit the utilization of concretes and at last lessens the development cost. Rice husk slag (RHA) which has the pozzolanic properties is a route forward. A relative report on impacts of solid properties when OPC of differing evaluations was mostly supplanted by RHA is examined in this paper. Rate supplanting of OPC with RHA was 0, 10, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The copper slag-contained asphalt mix has a high resistance to moisture and medium-to-long-term ageing [15]. The indirect tensile strength and resiliente modulus get increased for different temperatures (25 °C, 35 °C, 45 °C, 55 °C, and 60 °C) for the copper slag-contained asphalt mix when compared to the conventional asphalt mix [16]. From SEM analysis, it was found that there was no difference between the copper slag-incorporated asphalt mix and conventional asphalt mix [17].…”
Section: Introductionmentioning
confidence: 99%
“…The copper slag-contained asphalt mix has a high resistance to moisture and medium-to-long-term ageing [15]. The indirect tensile strength and resiliente modulus get increased for different temperatures (25 °C, 35 °C, 45 °C, 55 °C, and 60 °C) for the copper slag-contained asphalt mix when compared to the conventional asphalt mix [16]. From SEM analysis, it was found that there was no difference between the copper slag-incorporated asphalt mix and conventional asphalt mix [17].…”
Section: Introductionmentioning
confidence: 99%